1999
DOI: 10.1359/jbmr.1999.14.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Involvement of 17β-Estradiol in Intestinal Calcium Absorption Independent of 1,25-Dihydroxyvitamin D3 Level in the Rat

Abstract: The sex steroid 17␤-estradiol (17␤-E 2 ) has a broad range of actions, including effects on calcium and bone metabolism. This study with 3-month-old Brown Norway rats was designed to investigate the role of 17␤-E 2 in the regulation of calcium homeostasis. Rats were divided in four groups, sham-operated, ovariectomized (OVX), and OVX supplemented with either a 0.025-mg or 0.05-mg 17␤-E 2 pellet implanted subcutaneously. After 4 weeks, in none of the groups was serum calcium, phosphate, or parathyroid hormone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 64 publications
5
52
0
2
Order By: Relevance
“…This lack of age-dependent differences is in accordance with findings --gained with identical study design and methodology --in cattle and goat (Riner, 2006;Singer, 2006) and several other reports (Kinyamu et al, 1997;Wood et al, 1998;Lee et al, 2003;Pazianas et al, 2003;Yamagishi et al, 2006) and in contrast to data published elsewhere (Horst et al, 1990;Ebeling et al, 1992;Liang et al, 1994;Bischoff et al, 2001;Duque et al, 2002;Holick, 2003). Since an age and/or estrogen dependent impairment of calcium resorption was detectable in elder subjects in numerous studies, a resistance to vitamin D was postulated (Kinyamu et al, 1997;Wood et al, 1998) and furthermore vitamin D-dependent (Kinyamu et al, 1997;Liel et al, 1999;Schwartz et al, 2000;Leonard et al, 2001;Duque et al, 2002;Gilad et al, 2005) and independent effects of estrogens on calcium resorption were verified (Colin et al, 1999;Eisman, 2001;Van Cromphaut et al, 2003). Thus, in future studies hormone-and age-associated effects on calcium and vitamin D metabolism in sheep should be re-examined also in senescent dams with and without hormone substitution and evaluated separately.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This lack of age-dependent differences is in accordance with findings --gained with identical study design and methodology --in cattle and goat (Riner, 2006;Singer, 2006) and several other reports (Kinyamu et al, 1997;Wood et al, 1998;Lee et al, 2003;Pazianas et al, 2003;Yamagishi et al, 2006) and in contrast to data published elsewhere (Horst et al, 1990;Ebeling et al, 1992;Liang et al, 1994;Bischoff et al, 2001;Duque et al, 2002;Holick, 2003). Since an age and/or estrogen dependent impairment of calcium resorption was detectable in elder subjects in numerous studies, a resistance to vitamin D was postulated (Kinyamu et al, 1997;Wood et al, 1998) and furthermore vitamin D-dependent (Kinyamu et al, 1997;Liel et al, 1999;Schwartz et al, 2000;Leonard et al, 2001;Duque et al, 2002;Gilad et al, 2005) and independent effects of estrogens on calcium resorption were verified (Colin et al, 1999;Eisman, 2001;Van Cromphaut et al, 2003). Thus, in future studies hormone-and age-associated effects on calcium and vitamin D metabolism in sheep should be re-examined also in senescent dams with and without hormone substitution and evaluated separately.…”
Section: Resultsmentioning
confidence: 95%
“…Vitamin D receptors are also more abundant deep in crypts than in villar cells (Clemens et al, 1988). Results are, however, controversial in some instances (Berger et al, 1988;Sandgren et al, 1991;Kinyamu et al, 1997;Wood et al, 1998;Colin et al, 1999;Sheinin et al, 2000;Leonard et al, 2001;Lee et al, 2003;Pazianas et al, 2003;Chen et al, 2006). …”
mentioning
confidence: 99%
“…Ovarian hormone deficiency has been reported to impair gut calcium absorption in rats (21,24,25) and in post-menopausal women (26), whereas treatment with E 2 has been shown to stimulate absorption in rats (14,21) and in humans (27). In the EnR rats, uterine weights were significantly lower than those of control rats, indicating a reduced estrogenic activity with EnR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that estrogen deficiency after menopause is associated with increased renal Ca 2+ loss and intestinal Ca 2+ malabsorption, which can be corrected by estrogen replacement therapy (Colin et al 1999;Gennari et al 1990;Nordin et al 1991;Prince et al 1991). Therefore, the effect of estrogen on the proteins involved in active Ca 2+ (re)absorption was investigated.…”
Section: Estrogenmentioning
confidence: 99%
“…As previously mentioned, the deleterious effects of estrogen deficiency after menopause, leads to a negative Ca 2+ balance associated with renal Ca 2+ loss, intestinal Ca 2+ malabsorption and postmenopausal osteoporosis, which can be corrected with estrogen replacement therapy (Colin et al 1999;Nordin et al 1991;Prince et al 1991;Young and Nordin 1969). In addition, estrogen has been implicated in the protection against Ca 2+ nephrolithiasis via an increased reabsorption of Ca 2+ .…”
Section: Estrogens and Postmenopausal Osteoporosismentioning
confidence: 99%